2009
DOI: 10.1007/s10903-009-9299-7
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Metabolic Syndrome Risk Factors in Young Mexican and Mexican–American Women

Abstract: Little is known about effects of acculturation on disease risk in young Mexican and Mexican-American women living in a border community. The purpose of this study was to examine relationships between acculturation and features of metabolic syndrome (MetS) in Mexican and Mexican-American women (n = 60) living in the largest US-Mexico border community. Acculturation was measured by the short acculturation scale for Hispanics and birthplace. Body composition was measured by Bod Pod and daily physical activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…Although active subjects are less likely to suffer from MetS, these results are not significant compared to the sedentary group, suggesting that a main role is played by other factors, such as dietary pattern [34][35]. Accordingly, it was reported that fat mass, rather than inactivity, is an important contributor to disease risk in Mexican and Mexican–American women living on the US/Mexico border [36].…”
Section: Discussionmentioning
confidence: 91%
“…Although active subjects are less likely to suffer from MetS, these results are not significant compared to the sedentary group, suggesting that a main role is played by other factors, such as dietary pattern [34][35]. Accordingly, it was reported that fat mass, rather than inactivity, is an important contributor to disease risk in Mexican and Mexican–American women living on the US/Mexico border [36].…”
Section: Discussionmentioning
confidence: 91%
“…For example, in a study of Mexican women, the highly acculturated had higher BMI, fat mass, fasting insulin, and diastolic blood pressure than low-acculturated women [65]. …”
Section: Discussionmentioning
confidence: 99%
“…The SASH evaluates language use, media and ethnic social relations on a 5-pt Likert scale and has evaluated health outcomes [61] and acculturation [14, 62] in Mexican-American mothers. SASH has good reliability α=0.92 and higher scores indicate higher acculturation.…”
Section: Methodsmentioning
confidence: 99%